Deletion size analysis of 1680 22q11.2DS subjects identifies a new recombination hotspot on chromosome 22q11.2. (18th January 2018) - Guo, Tingwei; Diacou, Alexander; Nomaru, Hiroko; McDonald-McGinn, Donna M; Hestand, Matthew; Demaerel, Wolfram; Zhang, Liangtian; Zhao, Yingjie; Ujueta, Francisco; Shan, Jidong; Montagna, Cristina; Zheng, Deyou; et al.
Abstract: Recurrent, de novo, meiotic non-allelic homologous recombination events between low copy repeats, termed LCR22s, leads to the 22q11.2 deletion syndrome (22q11.2DS; velo-cardio-facial syndrome/DiGeorge syndrome). Although most 22q11.2DS patients have a similar sized 3 million base pair (Mb), LCR22A-D deletion, some have nested LCR22A-B or LCR22A-C deletions. Our goal is to identify additional recurrent 22q11.2 deletions associated with 22q11.2DS, serving as recombination hotspots for meiotic chromosomal rearrangements. Here, using data from Affymetrix 6.0 microarrays on 1680 22q11.2DS subjects, we identified what appeared to be a nested proximal 22q11.2 deletion in 38 (2.3%) of them. Using molecular and haplotype analyses from 14 subjects and their parent(s) with available DNA, we found essentially three types of scenarios to explain this observation. In eight subjects, the proximal breakpoints occurred in a small sized 12 kb LCR distal to LCR22A, referred to LCR22A+, resulting in LCR22A+-B or LCR22A+-D deletions. Six of these eight subjects had a nested 22q11.2 deletion that occurred during meiosis in a parent carrying a benign 0.2 Mb duplication of the LCR22A-LCR22A+ region with a breakpoint in LCR22A+. Another six had a typical de novo LCR22A-D deletion on one allele and inherited the LCR22A-A+ duplication from the other parent thus appearing on microarrays to have a nested deletion. LCR22A+ maps to an evolutionary breakpoint between mice and humans and appears to serve as a local hotspot for chromosome rearrangements on 22q11.2.